REVIEW ON OVARIAN CYSTS IN DAIRY CATTLE, ITS TREATMENT AND PREVENTION - FEKATA, ABERA (International Journal of Multidisciplinary Research and Studies, 2022)
The purpose of this paper was to examine ovarian cysts in dairy cattle, as well as their treatment and prevention options. Cysts are simply fluid-filled sacs surrounded by membranes, similar to grapes, and are most commonly seen in dairy cows in the first two months after calving. The development of large, persistent ovulatory follicles in the ovaries and the failure of a mature follicle to ovulate at the right period throughout the estrous cycle describe Ovarian Cysts (OC). The most common types of ovarian cysts in dairy cows are follicular cysts, luteinized cysts, and cystic corpora lutea. Ovarian cysts are usually connected with heredity, high milk production, age, lactation period, body condition score, seasonality, and phytoestrogens, yet the specific causes are unknown. Ovarian Cysts (OC) in dairy cows are diagnosed using a combination of history and clinical signs, transrectal palpation, ultrasonography, and plasma or milk progesterone assays. The main treatments for Cystic Ovarian Disease in dairy cows are Gonadotrophin Releasing Hormone (GnRH), Human Chorionic Gonadotrophin (HCG), and Prostaglandin F2 (PGF2). The economic losses of ovarian cysts are produced by an increase in the number of days open, an increase in the culling rate due to infertility, high treatment expenses, and a longer calving interval. Cystic ovarian disease is prevented through careful genetic selection, the elimination of bulls whose sire daughters have had cystic ovarian disease, and an appropriate diet.